2009
DOI: 10.3390/molecules14103881
|View full text |Cite
|
Sign up to set email alerts
|

Design of Antimicrobially Active Small Amphiphilic Peptide Dendrimers

Abstract: Novel polyfunctional small amphiphilic peptide dendrimers characterized by incorporation of a new core compounds – tris-amino acids or tetrakis-amino alcohols that originated from a series of basic amino acids – were efficiently synthesized. These new core elements yielded molecules with multiple branching and (+5)/(+6) charge at the 1-st dendrimer generation. Dendrimers exhibited significant antimicrobial potency against Gram(+) and Gram(-) strains involving also multiresistant reference strains (S. aureus AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Zhu et al [162] has recently tested the antimicrobial activity of a set of branched His-Lys dendrimers on Candida species and other fungi, finding that the four-branched dendrimer H2K4b was the most active among all. There are many other dendrimers that have been tested to be effective against a variety of bacterial strains, including multidrug-resistant strains [157,[224][225][226][227].…”
Section: Dendrimersmentioning
confidence: 99%
“…Zhu et al [162] has recently tested the antimicrobial activity of a set of branched His-Lys dendrimers on Candida species and other fungi, finding that the four-branched dendrimer H2K4b was the most active among all. There are many other dendrimers that have been tested to be effective against a variety of bacterial strains, including multidrug-resistant strains [157,[224][225][226][227].…”
Section: Dendrimersmentioning
confidence: 99%
“…According to other data on this subject, these results imply that structural factors such as distribution of charged and lipophylic groups determine antimicrobial and hemolytic properties. Thus, proper manipulation with these parameters may lead to the production of dendrimers with optimal qualities—high biological activity and low cytoxicity 107…”
Section: Antibacterial Propertiesmentioning
confidence: 99%
“…To challenge this problem many studies on potential antifungal dendrimers have been performed and yielded encouraging results. As in the case of bacteria, the mechanism of action underlying fungicidal properties of dendrimers is based on the interaction with the cell membrane which is followed by its disruption and cytoplasm leakage 107…”
Section: Antifungal Propertiesmentioning
confidence: 99%
“…The results are consistent with the hypothesis that both activities result from some common properties of the histidine-rich dendrimer peptide -their endosomal-disrupting properties. A number of other dendrimer peptides have been reported to be effective against a variety of bacterial strains including multidrug-resistant strains [60][61][62][63][64]. It is generally observed that bacterial resistance to peptides or the dendrimers develops much less than to standard antibiotics such as vancomycin.…”
Section: Peptide Dendrimers As Antimicrobial Agentsmentioning
confidence: 99%